A Novel Method for Comparison of Tissue Fibrosis after Inferior Turbinate Surgery: Ultrasound Elastography. Issue 1 (January 2015) - Gode, Sercan; Turhal, Goksel; Kismali, Erkan; Ozturk, Kerem; Midilli, Rasit
Background: Ultrasound (US) elastography has been widely used for thyroid, liver, and lymph nodes as a research tool in the current medical practice. It has been described in the inferior turbinates and validated as a reliable, reproducible, noninvasive, and objective method that can detect the fibrosis-related tissue strain. There is no previous study that investigated the amount of fibrosis induced by radiofrequency and bipolar electrocautery in the inferior turbinates in a noninvasive and objective manner. The aim of this study was to assess the amount of inferior turbinate soft tissue fibrosis that was induced by radiofrequency ablation (RFA) and submucosal bipolar diathermy (SBD) by US elastography. Methods: Thirty-eight inferior turbinates of 19 patients were included. RFA was applied to 18 inferior turbinates (group 1) and SBD was applied to 20 inferior turbinates (group 2). US elastography and visual analog scale (VAS) assessments were performed on all patients preoperatively and 6 months postoperatively. Results: Preoperative mean US elastography scores in groups 1 and 2 were 2.55 ± 0.78 m/s and 2.56 ± 0.49 m/s, respectively (p < 0.05). Postoperative mean US elastography scores in groups 1 and 2 were 2.91 ± 1.03 m/s and 3.41 ± 0.86 m/s, respectively (p < 0.05). Preoperative mean VAS scores in groups 1 and 2 were 2.78 ± 0.94 and 2.50 ± 1.15, respectively. Postoperative mean VAS scores in groups 1 and 2 were 6.61 ± 1.61 and 6.10 ± 1.4, respectively (p < 0.05). Correlation of US elastography and VAS scores was insignificant (p > 0.05). Conclusion: Both RFA and SBD of the inferior turbinates were effective in inducing scar tissue and, eventually, fibrosis in the soft tissue of inferior turbinates. Cauterization has been found to cause significantly higher amounts of fibrosis than radiofrequency; however, it did not reflect the comparable clinical outcome. This is the first study that objectively and noninvasively evaluates the targeted tissue fibrosis of the inferior turbinate surgeries by the novel inferior turbinate US elastography.